2017
DOI: 10.1111/resp.13066
|View full text |Cite
|
Sign up to set email alerts
|

CT‐determined pulmonary artery to aorta ratio as a predictor of elevated pulmonary artery pressure and survival in idiopathic pulmonary fibrosis

Abstract: Measurement of the PA:A is a useful and convenient method to predict elevated mPAP in IPF at initial evaluation. Moreover, a PA:A >0.9 was found to be an indicator of worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 33 publications
(76 reference statements)
4
37
0
Order By: Relevance
“…The relationship was significant, which is in line with previous reports [62][63][64][65]. However, in our study, PA size and PA:A ratio did not show a significant correlation with 6MWD, and, from this perspective, they may not serve as surrogates for RHC for the assessment of exercise capacity, until further, larger studies are obtained.…”
Section: Discussionsupporting
confidence: 77%
“…The relationship was significant, which is in line with previous reports [62][63][64][65]. However, in our study, PA size and PA:A ratio did not show a significant correlation with 6MWD, and, from this perspective, they may not serve as surrogates for RHC for the assessment of exercise capacity, until further, larger studies are obtained.…”
Section: Discussionsupporting
confidence: 77%
“…The PA/A is easily measured with good reproducibility without special software and is suitable for clinical routine use . Many studies have reported an association between a higher PA/A and poor prognosis in chronic lung diseases .…”
Section: Discussionmentioning
confidence: 99%
“…With regards to f‐ILD, Price et al emphasized the importance of the PA/A at stable disease stage in predicting early mortality . Judge et al described that pulmonary hypertension in f‐ILD was associated with an increased risk of AE and poor survival and other studies suggested the correlation between the PA/A and PA pressure . In some studies, the relationship between PA/A and pulmonary hypertension appears weaker in f‐ILD than in COPD .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning fibrosing ILDs [97], only CT automatic quantification of lung disease extent by means of a density mask is considered insufficient. To date, different methods for recognising a parenchymal pattern and its quantification have been suggested.…”
Section: Imagingmentioning
confidence: 99%